Left atrial shortening fraction to predict fetal cardiac abnormalities and dysfunction in gestational diabetes mellitus - Peng, Yu-Qing; Qiu, Xuan; Wang, Li; Li, Xin; Huo, Xiao-Yan (Frontiers in Cardiovascular Medicine, 2022)
Objective To evaluate the diagnostic efficiency of left atrial shortening fraction (LASF) in the detection of fetal cardiac abnormalities and dysfunction in patients with gestational diabetes mellitus (GDM). Methods In this study, we enrolled 256 pregnant women and divided them into GDM group (n = 156) and control group (n = 100). Fetal echocardiography was performed at 24–28 weeks of gestation to measure the LASF and interventricular septum (IVS) thickness. Based on IVS thickness, the GDM group was subdivided into the septal hypertrophy group (GDM I, n = 62) and non-septal hypertrophy group (GDM II, n = 94). LASF and IVS thickness were compared between the GDM and control groups and between GDM I and GDM II groups. Receiver operating characteristic (ROC) analysis was performed to determine the diagnostic accuracy of LASF in predicting septal hypertrophy. Results The GDM group had a larger IVS thickness (P < 0.05) but a lower LASF level (P < 0.001) than those of the control group. GDM I group had significantly lower LASF level than that in the GDM II group (P < 0.001). At 38.41% as the cutoff value, the LASF can predict septal hypertrophy with diagnostic sensitivity and specificity of 96.7% and 65.2%, respectively. Conclusion Fetal GDM are more likely to induce septal hypertrophy and ventricular dysfunction. LASF is a good indicator of septal hypertrophy or early diastolic dysfunction without septal hypertrophy.